Amides and Ethers as Chemoselective Surrogates for Copper(II)-Catalyzed ortho Benzoyloxylation of 2-Phenylpyridines - Yedage, Subhash L.; Bhanage, Bhalchandra M. (Synlett, 2015)
Chemoselective ortho benzoyloxylation of 2-phenylpyridine derivatives using amides and ethers as novel arylcarboxy sources using a Cu(II)/TBHP catalytic system has been reported. It is a simple protocol for ortho benzoyloxylation using amides and ethers as surrogates. A broad range of amides and ethers was found to be compatible under optimized reaction conditions to provide the corresponding products in good to excellent yield. The reaction proceeds through the cleavage of C–N, C–O, and C–H bonds and the formation of a new C–O bond via C–H functionalization.
Keywords: C–H activation; amide; ether; copper acetate; benzoyloxylation